Neonatal intra-atrial baffle repair for isolated ventricular inversion with left isomerism: a case report - Yuta Kuwahara; Yukihiro Takahashi; Yuya Komori; Naohiro Kabuto; Naoki Wada (Surgical Case Reports, 2020)
Abstract Background Discordant atrioventricular connection with concordant ventriculoarterial connection, otherwise known as isolated ventricular inversion (IVI), is an extremely rare congenital cardiac malformation. Reports on the corrective surgery for this anomaly in neonates are few, and the procedure is difficult and complicated. Herein, we report our use of atrial septostomy as a palliative procedure followed by corrective surgery for the repair of neonatal IVI with situs ambiguous(inversus) morphology. Case presentation A 2-day-old girl weighing 3.5 kg was admitted to our hospital with a low oxygen saturation (SpO2) of 70% She was diagnosed with IVI [situs ambiguous(inversus), D-loop, and D-Spiral], atrial septal defect, patent ductus arteriosus (PDA), interrupted inferior vena cava with azygos continuation to the left superior vena cava (SVC), and polysplenia by transthoracic echocardiography and cardiac computed tomography. We planned to perform corrective surgery and decided to first increase interatrial mixing by performing surgical atrial septostomy and PDA ligation 7 days after birth. However, despite the surgical septostomy, pulmonary venous blood flowed toward the right ventricle via the tricuspid valve rather than toward the left-sided atrium and hypoxemia persisted. We decided to perform the intra-atrial switch procedure at the age of 17 days via a re-median sternotomy. The cardiopulmonary bypass (CPB) circuit was established with ascending aorta and venous drainage through the SVC and hepatic veins. Utilizing a left-sided atrium(l-A) approach, a bovine pericardial patch was used for the intra-atrial baffle, which was trimmed into a trouser-shaped patch. Continuous suture using the patch was lying from the front of the right-sided upper pulmonary vein and rerouted SVC, hepatic vein, and coronary sinus to the tricuspid valve. Overall, CPB weaning proceeded smoothly; however, direct current cardioversion was performed for junctional ectopic tachycardia. The postoperative course was uneventful. Her postoperative SpO2 improved (approximately 99–100%); overall, the patient showed clinical improvement. Discharge echocardiography showed normal biventricular function and an intact atrial baffle with no venoatrial or atrioventricular obstruction. Conclusion We successfully performed an intra-atrial switch procedure for isolated ventricular inversion in a neonate. Long-term follow-up will be necessary to ensure the maintenance of optimal cardiac function.